2008 3rd International Symposium on Communications, Control and Signal Processing 2008
DOI: 10.1109/isccsp.2008.4537439
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Artificial Ants based feature extraction from wavelet packet coefficients for biomedical signal classification

Abstract: In this paper, a new feature extraction method utilizing ant colony optimization in the selection of wavelet packet transform (WPT) best basis is presented and adopted in classifying biomedical signals. The new algorithm, termed Intelligent Artificial Ants (IAA) searches the wavelet packet tree for subsets of features that best interact together thus producing high classification accuracies. While traversing the WPT tree, care is taken so that no redundancy in the information is selected by the Ants. The IAA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, SI algorithms have been used in biomedical data processing of biomedical data such as EEG and electrocardiogram (ECG) [19][20][21][22]. For instance, Cheng et al The first proposed algorithm within the ACO metaheuristic was the Ant System (AS) to solve the Travel Agent Problem (TSP) problem in which we search for the optimal route between a set of cities that the traveler must visit only once and return to the starting point.…”
Section: Ant Colony Optimization (Aco)mentioning
confidence: 99%
“…Recently, SI algorithms have been used in biomedical data processing of biomedical data such as EEG and electrocardiogram (ECG) [19][20][21][22]. For instance, Cheng et al The first proposed algorithm within the ACO metaheuristic was the Ant System (AS) to solve the Travel Agent Problem (TSP) problem in which we search for the optimal route between a set of cities that the traveler must visit only once and return to the starting point.…”
Section: Ant Colony Optimization (Aco)mentioning
confidence: 99%
“…where δ is a constant and J k is the fitness value of selected feature set by ant k [77]. By using this rule, the pheromone level of the features with highest fitness value will increase frequently, which will make that set more inclined to be selected during subsequent iterations by the ants.…”
Section: Improved Ant Colony Optimization Algorithm For Feature Selecmentioning
confidence: 99%
“…They have performed automated classification through ant colony approach (ACO_DTree algorithm) and the Group of Adaptive Models Evolution inductive models. Khushaba et al [151] proposed a new feature extraction method which utilizes ant colony optimization in the selection of wavelet packet transform (WPT) and adopted in classifying bio-medical signals.…”
Section: Aco In Eeg Signal Analysismentioning
confidence: 99%
“…Results show that the proposed method achieves a maximum accuracy of 83 %. Again, Khushaba et al [151] investigated the use of a combination of ACO and differential evolution called ANTDE for feature selection. They compare ANTDE, GA and BPSO, and reported that ANTDE's outperforms GA and BPSO due to the use of a mutual information based heuristic measure.…”
Section: Aco In Eeg Signal Analysismentioning
confidence: 99%